Robust in vitro propagation and regeneration of ubi kuning high beta carotene cassava genotype through somatic embryogenesis - SUPATMI SUPATMI; HANI FITRIANI; NURHAMIDARR RAHMAN; N. SRI HARTATI; ENNY SUDARMONOWATI (Nusantara Bioscience, 2017)
Supatmi, Fitriani H, Rahman N, Hartati NS, Sudarmonowati E. 2017. Robust in vitro propagation and regeneration of ubi kuning high beta carotene cassava genotype through somatic embryogenesis. Nusantara Bioscience 9: 352-360. Ubi kuning is a local genotype of cassava with high beta carotene content but the development of this genotype is still low because of plant disease susceptibility. Objectives of this study were to robust induce and regenerate somatic embryos of ubi kuning in vitro as well as to define a protocol of cyclic somatic embryogenesis of ubi kuning. Different size of leaf lobes, various concentration of picloram and different light conditions were tested to produce an effective and efficient somatic embryos (SEs).The best response of the induction of embryogenic callus was observed in leaf lobes explant with range size of 1-3 mm and >5mm cultured on induction medium (MS + 4% sucrose + 4 Î¼M CuSO4 + 0.1 mM Glutamine + 0.8% Microagar) supplemented with either 10 or 18 mg/L picloram grown under dark light for 4 weeks. Retransferring embryogenic callus to the same medium supplemented with 16 mg/L picloram gave the advanced development of primary somatic embryos (PSEs) after 70 d grown under both dark and light condition treatments. A positive correlation between globular and cotyledon stages was obtained in all treatments (Pâ‰¤ 0.01). The highest shoot and root growth (30% and 25%) was achieved in the regeneration of cotyledonary like-tissues cultured on callus embryogenic media (CEM) (MS basal+ 2.5 Î¼M CuSO4 + 3% sucrose + 2.75 g/L phytagel) supplemented with 1.6 mg/L of BAP (6-Benzylaminopurine).